2009
DOI: 10.1111/j.1365-2486.2009.02147.x
|View full text |Cite
|
Sign up to set email alerts
|

Recent drought stress leads to growth reductions in Larix sibirica in the western Khentey, Mongolia

Abstract: Trends in air temperature and precipitation in the forest-steppe ecotone of the western Khentey, northern Mongolia were studied and related to stem increment and shoot water relations in Mongolia's most common tree species, Siberian larch (Larix sibirica). The area has been subject to a significant increase of summer temperature and a decrease of summer precipitation during the last 47 years. Tree-ring width series from 4400 larch trees show a strongly decreasing annual increment since the 1940s. The onset of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
68
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 45 publications
10
68
0
2
Order By: Relevance
“…This finding points to a high vulnerability of the trees at the taiga's LT to climate warming. This conclusion is supported by ecophysiological, dendrochronological and palynological studies from the LT of the mountain taiga of western Khentei (Dulamsuren et al, 2009a(Dulamsuren et al, , 2010bSchlĂŒtz et al, 2008).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This finding points to a high vulnerability of the trees at the taiga's LT to climate warming. This conclusion is supported by ecophysiological, dendrochronological and palynological studies from the LT of the mountain taiga of western Khentei (Dulamsuren et al, 2009a(Dulamsuren et al, , 2010bSchlĂŒtz et al, 2008).…”
Section: Discussionsupporting
confidence: 61%
“…In the driest regions of western and southern Mongolia, no specific trends occurred at all. Based on tree-ring data, Dulamsuren et al (2010b) documented increasing drought stress for larch trees in the Khentei Mountains, which they attributed to increasing aridity caused by rising summer temperatures and decreasing summer precipitation during the last 50 years. Although trees at the outer boundary of the forest stands might be better adapted to drought stress, obvious margins of dead trees surrounding the forest islands were recently found in many places in the forest-steppe.…”
Section: Introductionmentioning
confidence: 99%
“…Previous year dry autumn weather conditions appeared to negatively affect larch growth rates. Increased summer droughts have been denoted in previous studies as being a key factor for reduced radial growth of larch trees across the northern hemisphere (Pederson et al 2001;Dulamsuren et al 2010b;Khishigjargal et al 2014;LĂ©vesque et al 2014). Khishigjargal et al (2014) found that recent increases in the frequency of summer droughts have promoted the frequency of growth anomalies such as narrow latewood.…”
Section: Discussionmentioning
confidence: 99%
“…In regions of the Selenge Aimag in Northern Mongolia, logging activity and high intensity fires caused larch forest area as pure or mixed-species to decrease, while increasing birch forest area (Gradel et al 2010). Larch forest degradation in the mountain forest steppe has been the subject of considerable research (Dulamsuren 2010a(Dulamsuren , 2010bDulamsuren et al 2011;Kishigjargal et al 2014). To our knowledge, no study has yet compared how Siberian larch and white birch are influenced by climatic factors.…”
Section: Introductionmentioning
confidence: 99%
“…Drought stress as a local factor impeding tree growth in recent decades has been supposed for different treeline environments (e.g. Lloyd and Fastie, 2002;Daniels and Veblen, 2004;Dulamsuren et al, 2010;Zhang et al, 2011;Fajardo and McIntire, 2012;Ohse et al, 2012).…”
Section: Tree Physiognomy and Growth Patternsmentioning
confidence: 99%